Multiphysics modelling of MICP grouting for drawdown control and curtain stability in confined aquifers with partially penetrating barriers during deep excavation - Sharif Nyanzi Alidekyi; Jianxiu Wang; Weiqiang Pan; Muhammad Arslan Ahmad; Yanxia Long; Naveed Sarwar Abbasi; Aamir Khan Mastoi (Computers and Geotechnics, 2027)

Self-healing concrete: investigating the synergistic effects of Bacillus subtilis and silica fume - Aayzaz Ahmed; Mirza Aamish Hassan Khan; Milica Vidak Vasić; Mehroz Imtiaz; Arslan Shabir; Tariq Ali; Muhammad Zeeshan Qureshi; Anwar Ahmed (European Journal of Environmental and Civil Engineering, 2026)

Lactic acid bacteria bacteriocins as novel antimicrobials against antibiotic-resistant Streptococcus pneumoniae in opthalamic infections - Marriam Wasif; Nazish Mazhar Ali; Syed Abdullah Mazhar; Sher Muhammad Zaman; Seher kiran; Maham Chaudhry; Ibtissem Louiz; Amor Hedfi; Manel Ben Ali; Arslan Muhammad Ali Khan; Itrat Zahra (Molecular Biology Reports, 2026)

Polymeric Based Bioinspired Microneedle Patch for the Treatment of Androgenetic Alopecia (AGA) - Muhammad Irfan Siddique; Shaher Bano; Muhammad Sarfraz; Arslan Ghazanfar; Talha Jawaid; Tahir Ali Chohan; Muhammad Naeem; Abida Khan (Journal of Pharmaceutical Innovation, 2026)

Molecular epidemiology and resistance modulation of Streptococcus spp. in subclinical goat mastitis in Pakistan - Ashraf Ali; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Hamza Rasheed; Maria Batool; Kehkshan Shahid; Gulbaz Anwar; Mahpara Safdar (Small Ruminant Research, 2026)

Molecular insights, resistance profiling, and in silico structural modeling of extended-spectrum beta-lactamase-producing E. coli in camels - Mahpara Safdar; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Kehkshan Shahid; Maria Batool; Gulbaz Anwar; Hamza Rasheed; Ashraf Ali (Veterinary Research Communications, 2026)

Predation, prey preference and switching behaviour of the soil predatory mite Blattisocius mali (Mesostigmata: Blattisociidae) on immature stages of Drosophila hydei - Muhammad Arslan Ibrahim; Katarzyna Michalska; Marcin Studnicki (Experimental and Applied Acarology, 2026)
Blattisocius mali is a soil predatory mite known to disperse phoretically on adult drosophilid fruit flies and feed ectoparasitically on them during transport. Despite this association, its behavioural and trophic interactions with immature drosophilid stages remain poorly understood. This study analysed B. mali ’s ability to prey on Drosophila hydei immature stages and examined the effects of prior rearing diet on predation, prey preference, and switching. Two types of predatory mite were compared: (1) fly-reared (FR) and (2) mite-reared (MR), raised on fruit flies or acarid mites, respectively. Predator females successfully attacked all developmental stages, except pupae, during 24 h of exposure in our assay. In non-choice tests, mean predation rates were highest on first-instar (L1), followed by eggs, second-instar (L2), and third-instar larvae (L3). FR predators, as compared to MR predators, showed the highest predation rates on all prey stages except L3. Feeding on fly eggs, B. mali exhibited significantly higher fecundity, laying nearly twice as many eggs compared to when they were fed on L1. Their oviposition declined markedly on L2 and L3. In two-choice and three-choice assays, B. mali showed a clear preference for eggs over larval instars in both predator types. FR predators preferred L1 over L2, while, conversely, MR predators preferred L2. Furthermore, B. mali females displayed different behaviour depending on the proportion of fly eggs and/or larvae available, including no switching, switching, or counter-switching. These findings improve understanding of trophic interactions between mesostigmatic mites and drosophilid flies and highlight the role of dietary experience in shaping predator foraging behaviour.

Turning trash into treasure: bioactive peptides from food waste–a decade of progress in extraction, purification, and applications: a systematic review - Muhammad Bilal; Muhammad Usman; Maratab Ali; Samee-Ullah; Faryal Shaukat; Muhammad Arslan; Zhihua Li; Xiaobo Zou; Yemin Guo; Xia Sun (Critical Reviews in Food Science and Nutrition, 2026)

Harnessing Biocompatible Bio-based Nanoprotectants for Phytohormone Modulation and Heavy Metal Detoxification in Sustainable Crop Production - Skhawat Ali; Ayesha Khalil Maan; Muhammad Arslan Yousaf; Yingying Zhou; Basharat Ali; Muhammad Kamran; Shoaib Ahmad; Mukesh Kumar Kanwar; Rafaqat Ali Gill; Weijun Zhou (Plant Science, 2026)

Comprehensive techno-economic assessment of commercial scale pyrolysis and co-pyrolysis plant of textile sludge and low-density polyethylene - Arslan Khan; Daniel Ciolkosz; Muhammad Safdar Ali; Waheed Miran; Imtiaz Ali (Process Safety and Environmental Protection, 2026)

Dual-loaded chitosan nanocarriers for sustainable management of Pseudomonas syringae in tomato: A critical narrative review and conceptual synthesis - Zeeshan Ahmad; Urooj Farid; Tauqeer Ahmed Qadri; Sana Azeem Kiani; Arslan Ali; Muhammad Nadeem Hassan; Humaira Yasmin (Physiological and Molecular Plant Pathology, 2026)

Antagonistic and synergistic interactions between Bacillus and Pseudomonas in the rhizosphere: Mechanistic basis, ecological constraints, and applications in plant growth promotion and disease suppression - Muhammad Mubeen; Bushra Mumtaz; Muhammad Umar Shafiq; Phyu Shin Thant; Tahir Mahmood; Muhammad Arslan Mushtaq; Sazada Siddiqui; Faisal Zulfiqar; Anam Moosa (Physiological and Molecular Plant Pathology, 2026)

Editorial Expression of Concern: Taurine decreases arsenic and microplastic toxicity in broccoli (Brassica oleracea L.) through functional and microstructural alterations - Shahar Yar; Muhammad Arslan Ashraf; Rizwan Rasheed; Umer Farooq; Arslan Hafeez; Shafaqat Ali; Mudassar Shahid; Pallab K. Sarker (BioMetals, 2026)

Foliar Application of Boric Acid Modulates the Morpho-Physiological Attributes and Health Risk Factors of Turnip (Brassica rapa L.) Under Nickel Accumulation Stress - Fizza Sajid; Tahrim Ramzan; Muhammad Shahbaz; Arslan Haider; Ejaz Ahmad Waraich; Sundas Qadeer (Journal of Soil Science and Plant Nutrition, 2026)

Redox homeostasis and trace metal regulation drive allantoin-induced tolerance against combined microplastic and cadmium stress in pea (Pisum sativum L.) - Anshra Murtaza; Muhammad Munir; Rizwan Rasheed; Muhammad Arslan Ashraf; Fakhar Abbas; Sarah Owdah Alomrani; Abdulrahman Alasmari; Shafaqat Ali; Sajjad Hassan Askari (Journal of Trace Elements in Medicine and Biology, 2026)

An efficient peroxymonosulfate activation by Nb2CTx-MXene mediated with CQDs composite catalyst for carbamazepine degradation: Kinetics and mechanistic insights - Muhammad Adnan; Zhenhua Zhao; Liling Xia; Ghulam Abbas Ashraf; Arslan Tauqeer; Muhammad Usman; Saqib Bashir; Thamer Alomayri; Akmal Abilkasimov (Journal of Environmental Sciences, 2026)

Evaluating the effect of Iron biofortification on nutraceutical and aromatic profiles of cereal grains: A case study of pearl millet - Hamza M.A. Abaker; Sulafa B.H. Hashim; Haroon Elrasheid Tahir; Muhammad Arslan; Gustav Komla Mahunu; Zhuhai Li; Xiaodong Zhai; Abdalbasit Adam Mariod; Mohammad Rezaul Islam Shishir; Magdi Ali Osman Mohammed; Ahmed Gaafar Mohammed Elgorashi; Alaa K.M. Khogly; et al. (Food Chemistry, 2026)

Green Synthesis of a ZnO@Sorghum Nano-Bioadsorbent for Enhanced Dye Wastewater Treatment - Muhammad Arslan Khalil; Bushra Sadia; Saima Noreen; Faisal Saeed Awan; Azeem Iqbal Khan; Muhammad Asif; Bilal Ahmad (Water, Air, & Soil Pollution, 2026)

Immunoinformatics-driven multi-epitope vaccine design as a promising strategy against multidrug-resistant pathogens: a comprehensive review - Rameen Nasir; Muhammad Mutayyab Javaid; Raheen Rahman; Rimsha Abbasi; Muneeb Khalid; Muhammad Arslan; Muhammad Amjad Sajjad; Ahsan Ibrahim (Folia Microbiologica, 2026)

Antimicrobial Plant Protein Patatin: Identification and In-Silico Analysis Through Phylogenetics and Molecular Docking - Sarah Tariq; Binish Khaliq; Hina Shaheen; Ahmad Riaz; Sumaira Rubbani; Muhammad Sajid Hamid Akash; Amjad Hussain; Muhammad Imran; Muhammad Arslan Javed; Ahmed Akrem; Sohaib Mehmood; Sajjad Azam (Agricultural Research, 2026)

Increased Atmospheric CO 2 Adversely Affects Large Pollinators, but Benefits Small Pollinators - Shahmshad Ahmed Khan; Muhammad Tanveer; Kit Prendergast; Taimoor Hussain; Arslan Shehryar; Asif Mehmood (Global Ecology and Biogeography, 2026)
Aim This study examines the impact of atmospheric CO 2 concentration on pollinator communities, focusing on body size‐related responses. It aims to understand how natural CO 2 variability influences pollinator abundance and diversity, and to assess potential ecological consequences for pollination services and ecosystem stability. Location The study was conducted across the Pothwar Plateau in Punjab, Pakistan, covering five districts: Murree, Rawalpindi/Islamabad, Jhelum, Chakwal and Attock. Time Period Field data were collected from September 2018 to May 2022, excluding December and January when pollinator activity was low. Major Taxa Studied The study focused on insect pollinators, including bees and hoverflies, and classified them into large‐ and small‐bodied groups based on size thresholds (e.g., bees were classified as large if their body length was ≥ 15 mm, and flies were classified as large if their body length was ≥ 10 mm). Methods A total of 25 study sites were randomly selected across an elevational gradient ranging from 350 to 2291 m. Atmospheric CO 2 concentrations were measured using a Temtop M2000 2nd digital meter at a standardized height of 1 m. Pollinator abundance and diversity were monitored using a transect‐based observation method (50 m transects, four per site). Sampling was conducted weekly from September to May, excluding December and January. Pollinators were identified in the field or collected for species‐level identification in the laboratory using morphological and image‐based techniques. Body size was measured using digital callipers. Statistical analyses were performed using Generalized Linear Mixed Models (GLMMs) to evaluate the relationship between pollinator populations, atmospheric CO 2 levels and other abiotic factors, while accounting for body size. Results A significant size‐dependent response to atmospheric CO 2 concentrations was observed. Larger‐bodied pollinators showed declines in abundance and diversity with increasing CO 2 levels, likely due to higher metabolic oxygen demands. In contrast, smaller‐bodied pollinators showed a positive association with elevated CO 2 concentrations. The relationship between CO 2 and pollinator communities remained consistent across different sites, confirming CO 2 as a reliable predictor variable. Main Conclusions Rising atmospheric CO 2 concentration could restructure pollinator communities by favouring smaller‐bodied species while negatively affecting larger‐bodied pollinators. This shift may have cascading effects on pollination networks and ecosystem stability. Conservation strategies should account for size‐specific vulnerabilities to climate‐induced CO 2 changes and prioritize protecting larger‐bodied pollinators, as they are more susceptible to CO 2 ‐related declines.

Exogenous Allantoin Attenuates Cadmium-Induced Toxicity in Rapeseed via Reducing Cd Accumulation and Modulating Antioxidant Defense Systems - Wenqiang Lan; Skhawat Ali; Mengting Lyu; Basharat Ali; Yiwa Hu; Muhammad Arslan Yousaf; Di He; Juanjuan Li; Yingying Zhou; Weijun Zhou (Journal of Plant Growth Regulation, 2026)

Comparative effect assessment of bisphenol analogs by high content analysis in zebrafish (Danio rerio) embryos - Muhammad Arslan Aslam; Riccardo Massei; Stefan Scholz (Aquatic Toxicology, 2026)

Bridging Lab to Land: Field Validation of Acinetobacter schindleri SR-5–1 for Nutrient Acquisition and Oxidative Stress Mitigation in Wastewater-Irrigated Pea (Pisum sativum L.) Plants - Sherjeel Hashmat; Muhammad Arslan Ashraf; Muhammad Tariq Javed; Umer Farooq; Mobeen Umer (Water, Air, & Soil Pollution, 2026)

Thiourea Mediated Improvement of Drought Stress in Maize (Zea Mays L.): Unrevealing Morpho-Physiological, Biochemical, and Root Attributes - Arslan Haider; Ejaz Ahmad Waraich; Surriya Bibi; Tahrim Ramzan; Muhammad Ahmad; Muhammad Faisal Maqsood (Journal of Soil Science and Plant Nutrition, 2026)

Mechanistic Insights into Silicon-Induced Modulation of Morphophysiological Traits and Plant Defense System in Mung Bean (Vigna Radiata L.) under Drought Stress - Mazhar Abbas; Ejaz Ahmad Waraich; Muhammad Ahmad; Nazia Ishfaq; Arslan Haider; Tahrim Ramzan; Muhammad Nazim; Usman Zulfiqar; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2026)

Paleocene stratigraphic framework and sedimentary architecture in the Sub-Himalayan Fold and Thrust Belt of Muzaffarabad, Pakistan: Depositional environment, Biotas, Paleogeographic and Economic Significance - Syed Kamran Ali; Arslan Sajjad; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Aamir Asghar; Aijaz Ali Halepoto; Evangelia Besiou; Assimina Antonarakou (Journal of Sedimentary Environments, 2026)

A machine learning framework for evaluating cyclic resistance of sands with non-plastic fines - Arslan Mushtaq; Muhammad Salman; Muhammad Noman; Muhammad Faizan; Afaq Ahmed (Innovative Infrastructure Solutions, 2026)

Mechanistic and Data-Guided Design of Biochar Adsorbents for Gas Phase Pollution Control: A State-of-the-Art Review - Hammad Khan; Muhammad Arshad; Ahsan Jalal; Ubaid Khalid; Arslan Maqbool; Mahvash Ansari; Sajjad Hussain (Environmental Science and Pollution Research, 2026)

A comprehensive review on nutritional, functional, and clinical perspectives of chia seeds and chia mucilage - Muhammad Arham Rauf; Maira Abdul Razzak; Fatima Waheed; Tabana Naz; Maham Fatima; Tanveer Ahmad; Muhammad Arslan; Usman Mir Khan; Mian Kamran Sharif (Bioactive Carbohydrates and Dietary Fibre, 2026)

Next-generation genome editing: no transgene, no tissue culture - Muhammad Arslan Mahmood; Julian R. Greenwood; Anthony A. Millar; Hendry Susila (Trends in Plant Science, 2026)

Comparative insights into molecular characterization and resistance profiling of methicillin-resistant Staphylococcus aureus across dairy livestock in Pakistan - Muhammad Ijaz; Maria Batool; Muhammad Umar Javed; Hamza Rasheed; Arslan Ahmed; Ali Abdullah Jabir; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2026)

Retraction Note: Assessment of genetic diversity in cotton genotypes using simple sequence repeat (SSR) markers: insights from interspecific and intraspecific variations - Muhammad Arslan; Akash Fatima; Fatima Javeria; Sehrish Ijaz; Umair Riaz; Gulnaz Saleem; Mounir M. Bekhit; Milad A. Mezher; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Integrated approach for arsenic prediction and health risk evaluation in community tube wells installed by public health department: comparative study of random forest, extreme gradient boosting, and deep neural networks - Ibad Ullah; Sebnem Arslan; Zahid Ullah; Zhanlong Chen; María V. Esteller; Hafiz Ullah; Muhammad Afaq Hussain; Waqar Ali; Rafique Ahmad (Environmental Geochemistry and Health, 2026)

Xanthan gum-stabilized cocoa butter emulsion: characterization, molecular interactions, physicochemical stability, and bioaccessibility of α-mangostin - Naymul Karim; Ke Zhang; Mohammad Rezaul Islam Shishir; Mohammad Nasiruddin Rana; Gobinath Marappan; Muhammad Arslan; Haroon Elrasheid Tahir; Li Zhihua; Xiaodong Zhai; Isam A. Mohamed Ahmed; Jitbanjong Tangpong; Xiaobo Zou (Food Chemistry, 2026)

Near-infrared, mid-infrared and Raman spectral feature information fusion strategy for multivariate quantitative analysis of polyphenols in Pakistani rice - Muhammad Arslan; Muhammad Zareef; Haroon Elrasheid Tahir; Muhammad Arslan; Allah Rakha; Zou Xiaobo (Food Control, 2026)

Optimisation of biomass-derived Propanol–Gasoline blends for sustainable bioenergy utilisation using response surface methodology - Muhammad Arslan Aslam; Ammar Hashmi; Muhammad Ashfaq; Muneeb-ur Rehman; Shah Nawaz Khan; Fakhar-ul Hasnain; Cheol Woo Park (Biomass and Bioenergy, 2026)

Efficacy of Foliar-applied Chitosan Nanoparticles in Enhancing Drought Tolerance of Maize (Zea Mays L.) Through Morpho-Physiological and Biochemical Modulation - Ayesha Rukhsar; Rana Muhammad Waqas; Sarfraz Ahmed; Nian Lili; Momal Munir; Abdul Razzaq; Muhammad Arslan Asghar; Muhammad Iqbal (Journal of Soil Science and Plant Nutrition, 2026)

Assessing the Efficacy of Exogenous Application of Glycine Betaine in Canola (brassica napus l.) Under Nickel Stress - Aneeza Muzafar; Muhammad Shahbaz; Tahrim Ramzan; Arslan Haider; Maha Fatima (Journal of Soil Science and Plant Nutrition, 2026)

Effects of biological and technical subsoil amelioration on root growth and crop performance in cereal crops - Muhammad Arslan; Roman Kemper; Thomas F. Döring; Oliver Schmittmann; Miriam Athmann (Soil and Tillage Research, 2026)

Large language models in building energy applications: a survey - Muhammad Arslan; Saba Munawar (Energy and Buildings, 2026)

Adaptive morphological and physiological strategies of Sporobolus ioclados in desert ecosystem - Muhammad Akram; Nargis Naz; Ummar Iqbal; Syeda Refat Sultana; Fahim Arshad; Muhammad Waheed; Muhammad Adeel Ghafar; Hafiz Muhammad Mohsin Hassan; Arslan Asghar; Abeer Hashem; Dalal Saad Alharbi; Graciela Dolores Avila-Quezada; et al. (The Science of Nature, 2026)

A Novel S‐Section Control Hose–Reel Machine for Variable Rate Fertigation - Yücel Tekin; Selçuk Arslan; Bere Benjamin Bantchina; Yahya Ulusoy; Kemal Sulhi Gündoğdu; Alexander Steiger; Ralf Bill; Görres Grenzdörffer; Muhammad Qaswar; Danyal Bustan; Samet Bıçaklar; Oğuzhan Akaltun; et al. (Irrigation and Drainage, 2026)
This study presents the development of a cloud‐based, automated variable‐rate fertigation system by modifying an existing hose–reel irrigation machine (HIM). A 46‐m‐wide HIM spraying boom was segmented into four independently controlled sections, and a 300‐L fertiliser tank was mounted on the spraying cart to deliver liquid fertiliser directly into each section line. A control system, programmed in C#, was designed to automate the application of irrigation water and fertiliser. Calibration through laboratory and field tests optimised the application accuracy. A cloud‐based information and communication technology platform was developed. The soil moisture data from the LSE01 sensors were transmitted via LoRaWAN to field gateways and then to the Things Network (TTN) for authentication, routing and JSON conversion. The system achieved precise irrigation and fertilisation within 15–50 mm and 80–600 L/ha, respectively, with minor errors (3–5% for irrigation, 1–3% for fertilisation). The spatial resolution improved significantly, with the lateral resolution reduced from 46 m to 10.7 m and the longitudinal resolution increased from 0.17 to 1.5 m, depending on the desired irrigation water and liquid fertiliser rates. These results demonstrate that the developed hose–reel variable‐rate fertigation machine offers accurate and efficient fertigation suitable for precision agriculture.

Harnessing Paramecium primaurelia for polyhydroxyalkanoate production: optimization of carbon sources for sustainable bioplastic synthesis - Ayesha Arshad; Itrat Zahra; Awais Ibrahim; Usama Shabbir; Shahid Nawaz; Ayesha Liaqat; Roohi Ijaz; Tuba Arooj; Sammi Rasheed; Ayesha Ghauri; Bushra Muneer; Amor Hedfi; et al. (Biologia, 2026)

Integration of mid and near-infrared spectroscopy for determining TPC and TFC in wheat varieties via multivariate analysis - Muhammad Zareef; Muhammad Arslan; Waqas Ahmad; Md Mehedi Hassan; Muhammad Naveed; Malik Muhammad Hashim; Sadaf Javaria; Quansheng Chen (Food Control, 2026)

pH-responsive MIL-101(Fe)/NiFe-LDH composite membranes for high-flux removal of cationic and anionic dyes in wastewater treatment - Shehriyar; Arslan Khurram; Abdul Jabbar; Muhammad Asim Khan; Wenhao Liu; Sadaf Mutahir; Akhtar Munir; Sameerah I. Al-Saeedi (Desalination, 2026)

Sustainable food packaging: Life cycle assessment, recycling innovations, and Pestalotiopsis microspora in biodegradable solutions - Muhammad Bilal; Muhammad Arslan; Suliman Khan; Jiyong Shi; Zhihua Li; Yemin Guo; Xia Sun; Zou Xiaobo (Trends in Food Science & Technology, 2025)

Sustainable biodiesel production via Alkanna tinctoria oil Conversion: A multi-method modeling approach utilizing crab shell-derived biochar catalysts - Ali Hamid; Hammad Khan; Arsalan Arif; Muhammad Arshad; Sajjad Hussain; Arslan Maqbool (Biomass and Bioenergy, 2025)

Impact of pairing gaps on β-decay properties and stellar electron capture rates - Jameel-Un Nabi; Arslan Mehmood; Muhammad Riaz (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Correction: Citrulline enhances salinity tolerance via photosynthesis, redox balance, osmotic and hormonal regulation, and nutrient assimilation in sunflower (Helianthus annuus L.) - Umer Farooq; Muhammad Arslan Ashraf; Rizwan Rasheed (Physiology and Molecular Biology of Plants, 2025)

Effect of citrulline seed priming on growth, photosynthesis, redox equilibrium, secondary metabolic enzymes, metal sequestration and nutrient acquisition in sunflower (Helianthus annuus L.) under chromium toxicity - Umer Farooq; Muhammad Arslan Ashraf; Muhammad Iqbal; Rizwan Rasheed (BioMetals, 2025)

Bacterial community of the shrimp (Litopenaeus vannamei) gut and its relationship with water quality in a recirculating aquaculture system (RAS) - Arslan Emmanuel; Bilal Raza; Muhammad Naeem Ramzan; Zhongming Zheng (Aquaculture International, 2025)

A smart olfactory visualization system based on colorimetric sensor array and chemometrics for the identification of rice adulteration - Muhammad Arslan; Muhammad Zareef; Mubrrah Afzal; Haroon Elrasheid Tahir; Jiyong Shi; Arslan Muhammad; Allah Rakha; Zou Xiaobo (Food Chemistry, 2025)

Monitoring indoor environmental conditions in office buildings using a sustainable Agentic RAG-LLM system - Muhammad Arslan; Saba Munawar; Lamine Mahdjoubi; Patrick Manu (Energy and Buildings, 2025)

Sustainable wastewater treatment via nitrogen/sulfur co-doped graphene composite: Mechanistic insights & process optimization - Humaira Seema; Muhammad Arshad; Arslan Maqbool; Sumbal Zeb; Ali Hamid; Muhammad Umar; Sajjad Hussain; Hammad Khan (Journal of Water Process Engineering, 2025)

Eco-friendly synthesis of N-doped carbon quantum dots from Bombax ceiba stem: A photophysical study with exploratory sensing of Fe3+/Cd2+ and dye degradation - Muhammad Arslan Akhtar; Jalwa Anum; Sameh S. Ahmed; Muhammad Ashfaq Ahmed; Asad Muhammad Khan; Christie M. Sayes; Abdur Rahim (Journal of Water Process Engineering, 2025)

Facile assembly of Bi2SiO5-SrTiO3 Z-scheme heterojunctions for enhanced photocatalytic CO2 conversion and pollutant degradation - Tingting Han; Yan Guo; Muhammad Arslan Mushtaq; Yuefa Jia (Journal of Environmental Chemical Engineering, 2025)

Amino acid-modified nano-magnetite boosts okra [Abelmoschus esculentus (L.) Moench] yield and iron enrichment for improved nutrition - Maham Ishfaq; Fahad Shafiq; Sumera Anwar; Muhammad Iqbal; Syed Hammad Raza; Arslan Mahmood; Muhammad Ashraf (BioMetals, 2025)

Empowering SMEs with SustainWater Bot to advance urban water sustainability - Muhammad Arslan; Saba Munawar; Zainab Riaz (Sustainable Cities and Society, 2025)

Green-synthesized amino-rich carbon quantum dots: A dual-function platform for fluorescent detection of heavy metals and degradation of malachite green dye - Jalwa Anum; Muhammad Arslan Akhtar; Asad Muhammad Khan; Khalid Ahmed; Christie M. Sayes; Ali Madi Almajwal; Jibran Iqbal; Abdur Rahim (Journal of Water Process Engineering, 2025)

Revisit the role of financial development on economic growth, human development, and sustainable development in higher-income countries - Muhammad Arslan Abdullah; Xiao Han; Muhammad Asif Amjad; Samariddin Makhmudov (Journal of Environmental Management, 2025)

Citrulline Reduces Copper Toxicity in Sunflower (Helianthus annuus L.) by Modulating Photosynthesis, Osmoregulation, Redox Homeostasis, and Nutrient Relations - Arslan Hafeez; Rizwan Rasheed; Muhammad Arslan Ashraf; Iqbal Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Exploring evolutionary perspectives and antibiogram analysis of biofilm-forming Staphylococcus aureus in goat mastitis - Muhammad Umar Javed; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Ali Abdullah Jabir; Maria Batool; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2025)

Gallic acid alleviates omeprazole-induced depressive behavior and memory impairment - Noreen Samad; Natasha Manzoor; Ali Irfan; Arslan Khalid; Umer Ejaz; Bakar Bin Khatab Abbas; Syed Aun Muhammad; Gamal A. Shazly; Saima Khaliq; Yousef A. Bin Jardan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Green and cost-effective photocatalytic degradation of murexide dye with acid catalyst - Zain Ul Abidin; Adnan Majeed; Muhammad Adnan Iqbal; Muhammad Kashif; Tabinda Fatima; Muhammad Yousif; Muhammad Arbaz; Syed Arslan Hussain; Muhammad Sajid (Clean Technologies and Environmental Policy, 2025)

Potential role of plant-derived thymol and carvacrol against Newcastle disease virus in poultry - Arslan Muhammad Ali Khan; Silla Ambrose; Rao Zahid Abbas (Archives of Microbiology, 2025)

Alleviating cadmium-induced stress in maize: the role of zinc sulphate application on growth and biochemical responses - Sadaf Saeed; Awais Manzoor; Arslan Haider; Tahrim Ramzan; Hafeez ur Rehman; Muhammad Ahmad; Shahzad Bashir; Usman Zulfiqar; Muhammad Nazim; Muhammad Faisal Maqsood; Waleed A. A. Alsakkaf; Hayssam M. Ali (Environmental Science and Pollution Research, 2025)

Efficacy of sustainable Nano Fillers on the viscoelastic behavior and energy absorption of 3D woven green composites - Muhammad Arslan Khalid; Tehseen Ullah; Khubab Shaker; Muzzamal Hussain; Muhammad Ayub Asghar; Muhammad Umair (Environment, Development and Sustainability, 2025)

Advanced characterization of hemp biomass pyrolysis: Bioenergy recovery and environmental implications - Rashid Minhas; Asif Hussain Khoja; Hajirah Kanwal; Muhammad Hassan; Arslan Khan; Syed Sheraz Daood; Israf Ud din; Ali Bahadar (Sustainable Chemistry and Pharmacy, 2025)

Citrulline enhances salinity tolerance via photosynthesis, redox balance, osmotic and hormonal regulation, and nutrient assimilation in sunflower (Helianthus annuus L.) - Umer Farooq; Muhammad Arslan Ashraf; Rizwan Rasheed (Physiology and Molecular Biology of Plants, 2025)

Exploring Synergistic Effects of Pantoea agglomerans BCH-1 and Bacillus pseudomycoides BCH-3 To Enhance Maize Adaptations Under Drought Condition - Anam Tariq; Mahwish Salman; Muhammad Arslan Ashraf; Shazia Anwer Bukhari; Ghulam Mustafa (Journal of Soil Science and Plant Nutrition, 2025)

Gamma-Aminobutyric Acid and Salicylic Acid Regulated Osmolyte Accumulation, Nutrient Acquisition, and ROS Metabolism to Decrease Arsenic Effects on Sunflower (Helianthus annuus L.) at Vegetative Stage - Muhammad Nawaz; Iqbal Hussain; Rizwan Rasheed; Muhammad Arslan Ashraf; Mahmood-ur-Rahman (Journal of Soil Science and Plant Nutrition, 2025)

Nitric Oxide and Hydrogen Peroxide Coordinate to Improve Photosynthesis, Oxidative Defense, Osmoregulation, and Ions Homeostasis in Pea (Pisum sativum L.) Under Drought - Muhammad Kamran Afzal; Noman Habib; Muhammad Arslan Ashraf; Qasim Ali; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2025)

How Deficit Irrigation and Salicylic Acid Treatments Affect Plant Growth and Fruit Production in Summer–Fall Production of ‘San Andreas’ Strawberry - Muhammad Ghaleb Dakheel; Izhar Ullah; Derviş Emre Doğan; Hakan Arslan; Leyla Demirsoy (Applied Fruit Science, 2025)

Development and Optimization of Stimuli-Responsive Fenugreek/Carrageenan-Co-poly (Methacrylate) Hydrogel Matrices for Controlled Delivery of 5-Fluorouracil - Muhammad Arslan; Muhammad Umer Ashraf; Ayman M. Al-Qaaneh; Aysha Aslam; Asif Mahmood; Hira Ijaz; Rai Muhammad Sarfraz; Mohamed M. Salem; Milad A. Mezher; Mounir M. Bekhit (AAPS PharmSciTech, 2025)

Metal sulfides in aged-coarse sands tailings facilitate naphthenic acids removal from oil sands process water - Muhammad Arslan; Muhammad Usman; Mohamed Gamal El-Din (Water Research, 2025)

Effects of neem leaf extract on physiochemical traits and antioxidant activity of peach fruit during storage - Jianhui Li; Muhammad Hanif; Muhammad Azam; Muhammad Arslan Khan; Muhammad Ali Umer; Beenish Chaudhary; Imtiaz Hussain; Tariq Aziz Khan; Shoaib ur Rehman; Muhammad Awais; Riadh Ilahy; Hongru Liu; et al. (Journal of Stored Products Research, 2025)

Extreme thermophilic microbial inoculation for reducing NH3 and N2O emissions in hyperthermophilic aerobic composting of refinery waste activated sludge - Xinge Fu; Hui Zuo; Zhouhao Wang; Pengyin Shang; Zhuoyu Li; Jin Li; Yali Zhan; Qinghong Wang; Muhammad Arslan; Mohamed Gamal El-Din; Chunmao Chen (Journal of Environmental Management, 2025)

Biological Approaches to Sustainable Management of Fusarium Wilt in Cotton - Iqra Javed; Muhammad Arslan Khan; Hasan Riaz; Shafqat Saeed; Muhammad Sajid; Muhammad Bashair; Zulqarnain Abbas; Haider Ali; Munirah Abdullah Al-Dosary; Muhammad Bilawal Junaid (Journal of Crop Health, 2025)

Taurine decreases arsenic and microplastic toxicity in broccoli (Brassica oleracea L.) through functional and microstructural alterations - Shahar Yar; Muhammad Arslan Ashraf; Rizwan Rasheed; Umer Farooq; Arslan Hafeez; Shafaqat Ali; Mudassar Shahid; Pallab K. Sarker (BioMetals, 2025)

Performance and Microbial Community Analysis of Integrated Bioremediation Systems with Photosynthetic Bacteria in Treating Mariculture Tailwater - Muhammad Naeem Ramzan; Ding Shen; Yingzhen Wei; Arslan Emmanuel; Wen Yang; Jinyong Zhu; Yangcai Wang; Zhongming Zheng (Journal of Ocean University of China, 2025)

Fish oil replacement with linseed oil affects growth, tissue fatty acid composition, blood chemistry, and antioxidant biomarkers in rohu, Labeo rohita - Muhammad Asghar; Noor Khan; Mahroze Fatima; Seyda Tacer-Tanas; Simon John Davies; Naveed ul Haque; Ayesha Tanveer; Murat Arslan (Aquaculture International, 2025)

RETRACTED ARTICLE: Assessment of genetic diversity in cotton genotypes using simple sequence repeat (SSR) markers: insights from interspecific and intraspecific variations - Muhammad Arslan; Akash Fatima; Fatima Javeria; Sehrish Ijaz; Umair Riaz; Gulnaz Saleem; Mounir M. Bekhit; Milad A. Mezher; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Nanoparticles as an Alternative Strategy to Control Foot and Mouth Disease Virus in Bovines - Rao Zahid Abbas; Silla Ambrose; Arslan Muhammad Ali Khan; Muhammad Mobashar; Khalil Mohamed (Biological Trace Element Research, 2025)

Systematic review of the digestive fate of rice phenolic compounds: Insights into bioavailability, influencing factors, encapsulation strategies, and health implications - Halah Aalim; Mohammad Rezaul Islam Shishir; Nermeen Yosri; Muhammad Arslan; Haroon Elrasheid Tahir; Sulafa B.H. Hashim; Naymul Karim; Xiaodong Zhai; Zhihua Li; Chenguang Zhou; Xiaobo Zou (Trends in Food Science & Technology, 2025)

Crosstalk between strigolactones and major hormones in plants under abiotic stresses - Farukh Ameen; Iqbal Hussain; Sunnia Afzal; Rizwan Rasheed; Muhammad Arslan Ashraf; Muhammad Iqbal (South African Journal of Botany, 2025)

From pollutant to purifier: Leveraging plastic waste-derived activated carbon for sustainable water remediation solutions - Hammad Khan; Muhammad Usama; Mohammad Ilyas Khan; Fazal Wahab; Izhar Ahmad; Ali Hamid; Sajjad Hussain; Arslan Maqbool (Journal of Environmental Management, 2025)

Unveiling the potential of Loigolactobacillus coryniformis BCH-4 to ameliorate drought stress in Zea mays L. - Anam Tariq; Mahwish Salman; Muhammad Arslan Ashraf; Muhammad Rizwan Javed; Abdul Tawab (World Journal of Microbiology and Biotechnology, 2025)

Antimicrobial resistance, virulence profiling, and drug repurposing analysis of Staphylococcus aureus from camel mastitis - Hamza Rasheed; Muhammad Ijaz; Arslan Ahmed; Muhammad Muddassir Ali (Veterinary Research Communications, 2025)

Nitrogen and phosphorus-related functional genes enhance nutrient removal in the integrated aquaculture wastewater bioremediation system in the presence of photosynthetic bacteria - Muhammad Naeem Ramzan; Ding Shen; Yingzhen Wei; Arslan Emmanuel; Regan Nicholaus; Wen Yang; Zhongming Zheng (Aquaculture International, 2025)

Thermokinetic investigation of Polyethylene Terephthalate (PET) plastic over biomass fly ash (BFA) catalyst using pyrolysis process through non-isothermal thermogravimetric analysis - Ali Raza; Waqar Ul Habib Khan; Asif Hussain Khoja; Arslan Khan; Muhammad Hassan; Rabia Liaquat; Majid Ali; Israf Ud Din; Abdulaziz Al-Anazi (Sustainable Chemistry and Pharmacy, 2024)

Catalytic strategies for CO2 hydrogenation to BTX and p-xylene: A sustainable approach towards carbon neutrality - Babar Ali; Muhammad Tahir Arslan; Ijaz Hussain; Yahuza Nantomah Abdulai; Khalid Alhooshani; Saheed Adewale Ganiyu (Journal of Environmental Chemical Engineering, 2024)

Characterization and identification of the key volatile and non-volatile substances of Vangueria madagascariensis J.F. Gmel fruits (Kirkir) and exploration of their binding interactions with olfactory and taste receptors using computational chemistry methodology - Haroon Elrasheid Tahir; Sulafa B.H. Hashim; Muhammad Arslan; Gustav Komla Mahunu; Mohammad Rezaul Islam Shishir; Li Zhihua; Suliman Khan; Abdalbasit Adam Mariod; Hamza A.M. Abaker; Howida Elkheir Ibrahim; Hesham R. El-Seedi; Zou Xiaobo (Food Chemistry, 2024)

Survival strategies and assembly mechanisms of microbial communities in petroleum-contaminated soils - Wenyi Lu; Yi Zheng; Yi Wang; Jiayu Song; Yibin Weng; Wenfeng Ma; Muhammad Arslan; Mohamed Gamal El-Din; Dingyuan Wang; Qinghong Wang; Chunmao Chen (Environmental Research, 2024)

Driving sustainable energy transitions with a multi-source RAG-LLM system - Muhammad Arslan; Lamine Mahdjoubi; Saba Munawar (Energy and Buildings, 2024)

Deciphering the differential expression patterns of yield-related negative regulators in hexaploid wheat cultivars and hybrids at different growth stages - Muhammad Jawad Akbar Awan; Muhammad Awais Farooq; Rubab Zahra Naqvi; Umer Karamat; Sayyad Ali Raza Bukhari; Muhammad Abu Bakar Waqas; Muhammad Arslan Mahmood; Muhammad Ismail Buzdar; Awais Rasheed; Imran Amin; Nasir A. Saeed; Shahid Mansoor (Molecular Biology Reports, 2024)

Exogenous Myo-inositol Weakens Salinity Effects by Improving Photosynthesis, ROS Homeostasis, Osmotic Adjustment, and Nutrient Acquisition in Maize (Zea mays L.) - Naheed Fatima; Muhammad Arslan Ashraf; Rizwan Rasheed; Mudassir Iqbal Shad; Shafaqat Ali (Journal of Plant Growth Regulation, 2024)

Therapeutic Potential of Green Synthesized Silver Nanoparticles for Promoting Wound-Healing Process in Diabetic Mice - Riffat Iqbal; Amna Asghar; Arslan Habib; Shaista Ali; Sadaf Zahra; Muhammad Imran Hussain; Ahmad Bilal Ahsan; Yulai Liang (Biological Trace Element Research, 2024)

Recent advances in delivering mangosteen-based phytochemicals using promising micro/nanocarriers: Formulation, outcomes, and perspectives - Naymul Karim; Mohammad Rezaul Islam Shishir; Gobinath Marappan; Suliman Khan; Sulafa B.H. Hashim; Halah Aalim; Muhammad Arslan; Haroon Elrasheid Tahir; Li Zhihua; Xiaodong Zhai; Md. Atiar Rahman; Jitbanjong Tangpong; et al. (Trends in Food Science & Technology, 2024)

Performance evaluation and microbial community succession analysis of co-composting treatment of refinery waste activated sludge - Xinge Fu; Hui Zuo; Yibin Weng; Zhouhao Wang; Yue Kou; Dingyuan Wang; Zhuoyu Li; Qinghong Wang; Muhammad Arslan; Mohamed Gamal El-Din; Chunmao Chen (Journal of Environmental Management, 2024)

Use of Metallic Nanoparticles Against Eimeria—the Coccidiosis-Causing Agents: A Comprehensive Review - Sahar Mustafa; Rao Zahid Abbas; Zohaib Saeed; Narjes Baazaoui; Arslan Muhammad Ali Khan (Biological Trace Element Research, 2024)

Corn yield prediction in site-specific management zones using proximal soil sensing, remote sensing, and machine learning approach - Bere Benjamin Bantchina; Muhammad Qaswar; Selçuk Arslan; Yahya Ulusoy; Kemal Sulhi Gündoğdu; Yücel Tekin; Abdul Mounem Mouazen (Computers and Electronics in Agriculture, 2024)

Allantoin regulated oxidative defense, secondary metabolism and ions homeostasis in maize (Zea mays L.) under heat stress - Humaira Yasmeen; Rizwan Rasheed; Muhammad Arslan Ashraf; Sadia Zafar; Shafaqat Ali (Physiology and Molecular Biology of Plants, 2024)

Growth, body composition, lipid profile, and peroxidation, physiological stress, and blood metabolic indicators in Labeo rohita fed a fish oil replacement with blended linseed and sunflower oils - Muhammad Asghar; Noor Khan; Mahroze Fatima; Murat Arslan; Simon John Davies; Naveed ul Haque (Aquaculture International, 2024)

Micro and nano-encapsulated natural products in yogurt: An emerging trend to achieve multifunctional benefits in product quality and human health. - Mohammad Rezaul Islam Shishir; Md Saifullah; Sulafa B.H. Hashim; Halah Aalim; Muhammad Bilal; Suliman Khan; Gobinath Marappan; Haroon Elrasheid Tahir; Li Zhihua; Xiaodong Zhai; Muhammad Arslan; Farah Saleena Taip; et al. (Food Hydrocolloids, 2024)

Impact of truncated modified basalt fibers on aerobic granular sludge stability and pollutant removal in piggery wastewater treatment - Yun Zhou; Xiaochun Wang; Muhammad Arslan; Xiangtong Zhou; Zhiren Wu; Jianxun Liu; Xueyan Li; Mohamed Gamal El-Din (Chemical Engineering Journal, 2024)

Seed Priming with Taurine Debilitates Copper Phytotoxic Effects by Maintaining Redox Balance, Ions Homeostasis and Photosynthetic Efficiency in Canola (Brassica napus L.) - Sadia Zafar; Rizwan Rasheed; Umer Farooq; Muhammad Arslan Ashraf; Shafaqat Ali; Mohammed Ali Alshehri; Khalid A. Al-Ghanim; Pallab K. Sarker (Journal of Soil Science and Plant Nutrition, 2024)

Exogenous Application of Silicon and Zinc Attenuates Drought Tolerance in Eruca sativa L. Through Increasing Chlorophyll Pigments, Osmoprotectants, and Modulating Defense Mechanisms - Iqbal Hussain; Atif Ayub; Airish Nayab; Muhammad Arslan Ashraf; Muhammad Arslan Ashraf; Sadam Hussain; Manzer H. Siddiqui; Muhammad Azeem Sabir; Usman Zulfiqar; Tanveer Hussain Khan (Journal of Plant Growth Regulation, 2024)

Desorption and migration of dissolved organics from oil sands tailings to capped water: Demonstration pit lake - Foroogh Mehravaran; Muhammad Arslan; Xiaoying Fan; Mohamed Gamal El-Din (Chemical Engineering Journal, 2024)

Molecular and microbial insights towards anaerobic biodegradation of anionic polyacrylamide in oil sands tailings - Jia Li; Muhammad Usman; Muhammad Arslan; Mohamed Gamal El-Din (Water Research, 2024)

Salicylic acid-driven innate antiviral immunity in plants - Muhammad Arslan Mahmood; Rubab Zahra Naqvi; Imran Amin; Shahid Mansoor (Trends in Plant Science, 2024)

Dual function of magnetic nanocomposites-based SERS lateral flow strip for simultaneous detection of aflatoxin B1 and zearalenone - Limei Yin; Jianrong Cai; Lixin Ma; Tianyan You; Muhammad Arslan; Heera Jayan; Xiaobo Zou; Yunyun Gong (Food Chemistry, 2024)

ZmGLK36 transcription factor bestows viral resistance in rice and wheat - Muhammad Arslan Mahmood; Julian R. Greenwood (Trends in Plant Science, 2024)

Novel layered BiO2-x: Applications, developments and challenges in photocatalysis - Yi Luo; Tingting Han; Hongru Han; Muhammad Arslan Mushtaq; Yuefa Jia; Gangqiang Zhu (Journal of Environmental Chemical Engineering, 2024)

The potential effects of N-Acyl homoserine lactones on aerobic sludge granulation during phenolic wastewater treatment - Shasha Liu; Qinghong Wang; Jiahao Liang; Jin Li; Zhiguo Shao; Yehua Han; Muhammad Arslan; Mohamed Gamal El-Din; Zhuoyu Li; Chunmao Chen (Environmental Research, 2024)

Thiamine Regulated Osmolyte Accumulation, Nutrient Acquisition, and ROS Metabolism to Lessen Salinity Effects on Wheat (Triticum aestivum L.) - Sunaira Urooj; Rizwan Rasheed; Muhammad Arslan Ashraf; Shafaqat Ali; Iqbal Hussain (Journal of Soil Science and Plant Nutrition, 2024)

Salicylic Acid-Induced Antioxidant Defense System Alleviates Cadmium Toxicity in Wheat - Umer Hayat; Kaleem ul din; Arslan Haider; Tahrim Ramzan; Bilal Ahmad Shahzad; Muhammad Ahmad; Usman Zulfiqar; Muhammad Faisal Maqsood; Sadam Hussain; Mona S. Alwahibi; Mohamed S. Elshikh (Journal of Soil Science and Plant Nutrition, 2024)

Correction: Taurine Enervates Nickel Stress in Lagenaria siceraria by Regulating Redox Balance, Methylglyoxal Detoxification, H2S Production, and Nickel Uptake - Arslan Hafeez; Rizwan Rasheed; Muhammad Rizwan; Noman Habib; Sadia Zafar; Mudassir Iqbal Shad; Shafaqat Ali; Muhammad Arslan Ashraf (Journal of Soil Science and Plant Nutrition, 2024)

Taurine Enervates Nickel Stress in Lagenaria siceraria by regulating Redox Balance, Methylglyoxal Detoxification, H2S Production, and Nickel Uptake - Arslan Hafeez; Rizwan Rasheed; Muhammad Rizwan; Noman Habib; Sadia Zafar; Mudassir Iqbal Shad; Shafaqat Ali; Muhammad Arslan Ashraf (Journal of Soil Science and Plant Nutrition, 2024)

Pervasive influence of heavy metals on metabolic pathways is potentially relieved by hesperidin to enhance the phytoremediation efficiency of Bassia scoparia - Mazhar Hussain; Arslan Hafeez; Muhammad Rizwan; Rizwan Rasheed; Mahmoud F. Seleiman; Muhammad Arslan Ashraf; Shafaqat Ali; Umer Farooq; Muhammad Nafees (Environmental Science and Pollution Research, 2024)

Exploring nature's filters: Peat-mineral mix for low and high-strength oilfield produced water reclamation - Muhammad Arslan; Muhammad Usman; Mohamed Gamal El-Din (Water Research, 2024)

Microbial goldmine: Investigating probiotic floral diversity in human breast milk - Ayesha Saeed; Azra Yasmin; Mehreen Baig; Maryam Pervaiz; Muhammad Arslan Ahmed; Muhammad Tabish; Humaira Hashmat (Bioactive Carbohydrates and Dietary Fibre, 2024)

Assessment of heavy metals level in chicken with indeterminate analysis in localities of Lahore, Pakistan - Naveed Ahmad; Usama Afzal; Ramna Zafar; Muhammad Arslan; Saira Riaz; Shahzad Naseem; Muhammad Naeem; Adeena Fatima; Mubashar Ali; Muhammad Aslam (Environmental Monitoring and Assessment, 2024)

Appraisal of the health hazards associated with the ingestion of vegetables contaminated with potentially toxic elements - Ali Afzal; Atif Muhmood; Syed Ayyaz Javed; Arslan Nazarat; Muhammad Rashid; Asrar Hussain Shah; Farhana Siddique (Arabian Journal of Geosciences, 2024)

From reporting to responsibility: investigating the influence of sustainability disclosure on earnings management - Kamran Ali; Hafiz Muhammad Arslan; Muhammad Mubeen; Hafiz Azeem; Zhao Zhen-Yu; Jiang Yushi; Miao Miao (Environment, Development and Sustainability, 2024)

Methyl-salicylate (MeSA)-mediated airborne defence - Muhammad Arslan Mahmood; Muhammad Jawad Akbar Awan; Rubab Zahra Naqvi; Shahid Mansoor (Trends in Plant Science, 2024)

Remediation of phenanthrene-contaminated soil by iron oxide/carboxylate-rich porous carbon composites from vinegar residue - Zhijun Luo; Huan Luo; Lingling Qu; Pamela Chelme-Ayala; Muhammad Arslan; Mohamed Gamal El-Din (Journal of Environmental Chemical Engineering, 2024)

Shear strengthening of precast prestressed bridge I-girders using shape memory reinforcement - Muhammad Arslan Yaqub; Christoph Czaderski; Stijn Matthys (Engineering Structures, 2024)

Correction to: Differential responses of Brassica napus cultivars to dual effects of magnesium oxide nanoparticles - Sharafat Ali; Zaid Ulhassan; Skhawat Ali; Zohaib Kaleem; Muhammad Arslan Yousaf; Mohamed S. Sheteiwy; Shafaqat Ali; Muhammad Waseem; Sanaullah Jalil; Jian Wang; Weijun Zhou (Environmental Science and Pollution Research, 2024)

The nexus between green intellectual capital, blockchain technology, green manufacturing, and sustainable performance - Muhammad Umar; Arslan Ahmad; Robert Sroufe; Zikri Muhammad (Environmental Science and Pollution Research, 2024)

Differential responses of Brassica napus cultivars to dual effects of magnesium oxide nanoparticles - Sharafat Ali; Zaid Ulhassan; Skhawat Ali; Zohaib Kaleem; Muhammad Arslan Yousaf; Mohamed S. Sheteiwy; Shafaqat Ali; Muhammad Waseem; Sanaullah Jalil; Jian Wang; Weijun Zhou (Environmental Science and Pollution Research, 2024)

Trade agreements and CO2 emissions in Asian countries: accounting for institutional heterogeneity - Mehboob Ul Hassan; Arslan Tariq Rana; Muhammad Khan; Samreen Gillani (Environmental Science and Pollution Research, 2024)

Phytochemical screening and antimicrobial potential of Chenopodium quinoa extract against pathogenic bacterial strains - Hina Anwar; Arslan Habib; Muhammad Usman Taj; Muhammad Azhar Ali; Ayesha Munir; Marva Shafi; Maria Saddique; Sohaib Ahmed; Henrique D. M. Coutinho (Vegetos, 2024)

Microbial activity, community composition and degraders in the glyphosate-spiked soil are driven by glycine formation - Sohaib Aslam; Muhammad Arslan; Karolina M. Nowak (Science of The Total Environment, 2024)

First report on genotypic estimation of MRSA load in udder of nomadic sheep flocks affected with subclinical mastitis in Pakistan - Muhammad Jawad Sabir; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Muhammad Umar Javed; Farwa Anwaar (Research in Veterinary Science, 2024)

Co-application of copper nanoparticles and metal tolerant Bacillus sp. for improving growth of spinach plants in chromium contaminated soil - Arslan Ali; Suliman Mohammed Suliman Alghanem; Haifa Abdulaziz Sakit Al-Haithloul; Saima Muzammil; Muhammad Adrees; Effa Irfan; Muhammad Waseem; Alia Anayat; Muhammad Saqalein; Muhammad Rizwan; Shafaqat Ali; Amany H.A. Abeed (Chemosphere, 2023)

HPLC-DAD, GC–MS, UHPLC-Q-TOF/MS2, ICP-MS and FT-NIR combined with the chemometrics explain seasonal variation in Cassia senna L. leaves from the coast of Red Sea in Sudan - Haroon Elrasheid Tahir; Sulafa B.H. Hashim; Muhammad Arslan; Gustav Komla Mahunu; Huang Xiaowei; Li Zhihua; Abdalbasit Adam Mariod; Isameldeen I.H. Abdalla; Hesham R. El-Seedi; Ahmed Abdel Aziz Ahmed; Zou Xiaobo (South African Journal of Botany, 2023)

Lithium-induced alterations in soybean nodulation and nitrogen fixation through multifunctional mechanisms - Noman Shakoor; Muzammil Hussain; Muhammad Adeel; Imran Azeem; Muhammad Arslan Ahmad; Muhammad Zain; Peng Zhang; Yuanbo Li; Wang Quanlong; Robert Horton; Yukui Rui (Science of The Total Environment, 2023)

Dual-layers Raman reporter-tagged Au@Ag combined with core-satellite assemblies for SERS detection of Zearalenone - Limei Yin; Tianyan You; Muhammad Arslan; Hesham R. El-Seedi; Zhiming Guo; Xiaobo Zou; Jianrong Cai (Food Chemistry, 2023)

A renewable and sustainable framework for clean fuel towards circular economy for solid waste generation in leather tanneries - Arshid Mahmood Ali; Arslan Khan; Muhammad Shahbaz; Muhammad Imtiaz Rashid; Muhammad Imran; Khurram Shahzad; Aishah Binti Mahpudz (Fuel, 2023)

Development of ZnO-GO-NiO membrane for removal of lead and cadmium heavy metal ions from wastewater - Arslan Maqbool; Ameen Shahid; Zaib Jahan; Muhammad Bilal Khan Niazi; Muhammad Ali Inam; Ahmed M. Tawfeek; Emadeldin M Kamel; Muhammad Saeed Akhtar (Chemosphere, 2023)

Assessment of thermokinetic behaviour of tannery sludge in slow pyrolysis process through artificial neural network - Arslan Khan; Imtiaz Ali; Salman Raza Naqvi; Hamad AlMohamadi; Muhammad Shahbaz; Arshid Mahmood Ali; Khurram Shahzad (Chemosphere, 2023)

Modifying engineered nanomaterials to produce next generation agents for environmental remediation - Muhammad Arslan Ahmad; Muhammad Adeel; Noman Shakoor; Rabia Javed; Muhammad Ishfaq; Yutao Peng; Muhammad Zain; Imran Azeem; Ilyas Ali; Muhammad Usman; Zihao Wu; Gholamreza Gohari; et al. (Science of The Total Environment, 2023)

Enhancing efficiency of biological contact oxidation reactors through filaments optimization of basalt fibers bio-carriers: Insights from a pilot-scale study - Huicheng Ni; Muhammad Arslan; Tiancai Zhang; Lizhuang Chen; Yaping Wang; Junchao Qian; Fu Cao; Zhiren Wu; Mohamed Gamal El-Din (Journal of Water Process Engineering, 2023)

Building occupancy number prediction: A Transformer approach - Kailai Sun; Irfan Qaisar; Muhammad Arslan Khan; Tian Xing; Qianchuan Zhao (Building and Environment, 2023)

Novel sol–gel synthesis of Mo-doped ZnO-NPs for photo-catalytic waste water treatment using the RhB dye as a model pollutant - Muhammad Sohaib; Tahir Iqbal; Sumera Afsheen; M. B. Tahir; Arslan Masood; Muhammad Rafique; K. N. Riaz; M. A. Sayed; A. F. Abd El-Rehim; Atif Mossad Ali (Environment, Development and Sustainability, 2023)

Allantoin alleviates chromium phytotoxic effects on wheat by regulating osmolyte accumulation, secondary metabolism, ROS homeostasis and nutrient acquisition - Rizwan Alam; Rizwan Rasheed; Muhammad Arslan Ashraf; Iqbal Hussain; Shafaqat Ali (Journal of Hazardous Materials, 2023)

Catalytic pyrolysis of rice husk over defect-rich beta zeolites for biofuel production - Ali Azfar Zaidi; Arslan Khan; Hamad AlMohamadi; Muhammad Waqas Anjum; Imtiaz Ali; Salman Raza Naqvi; Shinya Kokuryo; Koji Miyake; Norikazu Nishiyama (Fuel, 2023)

Taurine protected Trifolium alexandrinum L. plants from damages of individual and interactive effects of chromium and drought stress - Muhammad Arslan Ashraf; Rizwan Rasheed; Iqbal Hussain; Mudassir Iqbal Shad; Wajeeha Nazim (Acta Physiologiae Plantarum, 2023)

Coumarin regulated redox homeostasis to facilitate phytoremediation of saline and alkaline soils by bitter gourd (Momordica charantia L.) - Kamila Iram; Muhammad Arslan Ashraf; Sobhy M. Ibrahim; Rizwan Rasheed; Shafaqat Ali (Environmental Science and Pollution Research, 2023)

WeiTsing: A guard of the stele - Muhammad Arslan Mahmood; Rubab Zahra Naqvi; Shahid Mansoor (Molecular Plant, 2023)

Modulating hydrophilic properties of β-cyclodextrin/carboxymethyl cellulose colloid particles to stabilize Pickering emulsions for food 3D printing - Ziang Guo; Zhihua Li; Shaoyi Cen; Nini Liang; Arslan Muhammad; Haroon Elrasheid Tahir; Jiyong Shi; Xiaowei Huang; Xiaobo Zou (Carbohydrate Polymers, 2023)

Effect of exogenous taurine on growth, oxidative defense, and nickel (Ni) uptake in canola (Brassica napus L.) under Ni stress - Muhammad Arslan Ashraf; Arslan Hafeez; Rizwan Rasheed; Iqbal Hussain; Umer Farooq; Muhammad Rizwan; Shafaqat Ali (Physiology and Molecular Biology of Plants, 2023)

Editorial: Occurrence, migration and degradation of emerging organic pollutants in the estuarine environment - Qing Luo; Muhammad Adeel; Muhammad Arslan Ahmad; Guangzhe Jin; Muhammad Zain (Frontiers in Marine Science, 2023)

Effect of seed priming by taurine on growth and chromium (Cr) uptake in canola (Brassica napus L.) under Cr stress - Muhammad Arslan Ashraf; Sobhy M. Ibrahim; Rizwan Rasheed; Muhammad Rizwan; Iqbal Hussain; Shafaqat Ali (Environmental Science and Pollution Research, 2023)

Performance of constructed floating wetlands in a cold climate waste stabilization pond - Muhammad Arslan; Sarah Wilkinson; M. Anne Naeth; Mohamed Gamal El-Din; Zimran Khokhar; Christopher Walker; Terry Lucke (Science of The Total Environment, 2023)

Evaluation of Physio-Morphological and Biochemical Responses for Salt Tolerance in Wheat (Triticum aestivum L.) Cultivars - Muhammad Arslan Ashraf; Arslan Hafeez; Rizwan Rasheed; Iqbal Hussain; Umer Farooq; Muhammad Rizwan; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Physiological effects of some engineered nanomaterials on radish (Raphanus sativus L.) intercropped with pea (Pisum sativum L.) - Mehr-un-Nisa; Fahad Shafiq; Sumera Anwar; Arslan Mahmood; Muhammad Iqbal; Kaleem Ullah; Muhammad Zulqarnain; Imtiaz Haider; Muhammad Ashraf; Lixin Zhang (Environmental Science and Pollution Research, 2023)

Improving Lignin Metabolism, Lodging Resistance, and Yield of Rapeseed (Brassica napus L.) by Applying Straw-Fermented Fertilizer - Yue Hu; Hafiz Hassan Javed; Yong-Li Du; Qi-Wen Liao; Wen Ye; Jing Zhou; Xiao Peng; Muhammad Arslan; Ali Raza; Yong-Cheng Wu (Journal of Soil Science and Plant Nutrition, 2023)

Allicin Decreases Phytotxic Effects of Petroleum Hydrocarbons by Regulating Oxidative Defense and Detoxification of Cytotoxic Compounds in Wheat - Muhammad Arslan Ashraf; Rizwan Rasheed; Iqbal Hussain; Freeha Fatima Qureshi; Muhammad Rizwan; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Potential Breeding Strategies for Improving Salt Tolerance in Crop Plants - Muhammad Afzal; Salah El Sayed Hindawi; Salem Safer Alghamdi; Hussein H. Migdadi; Muhammad Altaf Khan; Muhammad Usama Hasnain; Muhammad Arslan; Muhammad Habib ur Rahman; Muhammad Sohaib (Journal of Plant Growth Regulation, 2023)
Salinity is one of the significant abiotic stresses that negatively affect plant production processes, growth, and development, which ultimately reduce yield. Plants adapt specific mechanisms to withstand saline conditions and activate diverse salt tolerance genes to counter osmotic and oxidative stresses induced by salinity. Genetic development in salinity tolerance is quite complex, while advancement has made less progress than expectation over the past few decades. Generating an explosion of genetics- and genomics-related information and technology in recent decades pledge to deliver innovative and advanced resources for the potential production of tolerant genotypes. Despite considerable progress in defining the primary salinity tolerance mechanisms, main obstacles are yet to be solved in the translation and incorporation of the resulting molecular knowledge into the plant breeding activities. Diverse approaches are proposed to enhance plant breeding efficacy to increase plant productivity in saline environments. Understanding the genetics of salt tolerance is a difficult task because multiple genes and pathways are involved. Important advances in tools and methods for updating and manipulating plant genomics knowledge provide detailed insights and dissect the salinity tolerance mechanism accomplished by the breeding goals. Genome-wide analyses (GWA) identify SNP variations and functional effects that appear to be the way of the future for developing salinity-tolerant plants. Gene discovery to manipulate the molecular mechanisms which underlie the complex phenotype of salinity tolerance methods, identification of genes, QTL, association mapping, linkage, and functional genomics, such as transcript identifying and proteins related to salinity, is necessary. The present analysis also discussed some of the opportunities and challenges, focusing on molecular breeding strategies used in conjunction with other crop development approaches to growing elite salt-tolerant lines.

PASTE: a high-throughput method for large DNA insertions - Muhammad Jawad Akbar Awan; Muhammad Arslan Mahmood; Rubab Zahra Naqvi; Shahid Mansoor (Trends in Plant Science, 2023)

Classification of Black Mahlab seeds (Monechma ciliatum) using GC–MS and FT-NIR and simultaneous prediction of their major volatile compounds using chemometrics - Haroon Elrasheid Tahir; Abdalbasit Adam Mariod; Sulafa B.H. Hashim; Muhammad Arslan; Gustav Komla Mahunu; Huang Xiaowei; Li Zhihua; Isameldeen I.H. Abdalla; Zou Xiaobo (Food Chemistry, 2023)

FDI and CO2 emissions in developing countries: the role of human capital - Muhammad Khan; Arslan Tariq Rana; Wafa Ghardallou (Natural Hazards, 2023)

Vegetable oils as bio-based precursors for epoxies - Fareeha Marriam; Adnan Irshad; Isra Umer; Muhammad Arslan Asghar; Muhammad Atif (Sustainable Chemistry and Pharmacy, 2023)

Effect of exogenous taurine on pea (Pisum sativum L.) plants under salinity and iron deficiency stress - Muhammad Arslan Ashraf; Rizwan Rasheed; Muhammad Rizwan; Iqbal Hussain; Ramish Aslam; Freeha Fatima Qureshi; Barira Shoukat Hafiza; Rohina Bashir; Shafaqat Ali (Environmental Research, 2023)

Effect of Metals or Trace Elements on Wheat Growth and Its Remediation in Contaminated Soil - Iqbal Hussain; Sunnia Afzal; Muhammad Arslan Ashraf; Rizwan Rasheed; Muhammad Hamzah Saleem; Aishah Alatawi; Farukh Ameen; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Novel mesoporous silica surface loaded gold nanocomposites SERS aptasensor for sensitive detection of zearalenone - Zhiming Guo; Lingbo Gao; Limei Yin; Muhammad Arslan; Hesham R. El-Seedi; Xiaobo Zou (Food Chemistry, 2023)

Exogenous Coumarin Decreases Phytotoxic Effects of Manganese by Regulating Ascorbate–Glutathione Cycle and Glyoxalase System to Improve Photosynthesis and Nutrient Acquisition in Sesame (Sesamum indicum L.) - Mudassir Iqbal Shad; Muhammad Arslan Ashraf; Rizwan Rasheed; Iqbal Hussain; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2023)

Silicon Enhances Morpho–Physio–Biochemical Responses in Arsenic Stressed Spinach (Spinacia oleracea L.) by Minimizing Its Uptake - Muhammad Hamzah Saleem; Manar Fawzi Bani Mfarrej; Aishah Alatawi; Sahar Mumtaz; Muhammad Imran; Muhammad Arslan Ashraf; Muhammad Rizwan; Kamal Usman; Parvaiz Ahmad; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Current knowledge and implementations of Bemisia tabaci genomic technologies for sustainable control - Muhammad Arslan Mahmood; Rubab Zahra Naqvi; Hamid Anees Siddiqui; Imran Amin; Shahid Mansoor (Journal of Pest Science, 2023)

Characterization of Azadirachta indica synthesized silver nanoparticles and its toxicity against Dusky cotton bug, Oxycarenus hyalinipennis Costa (Hemiptera:Lygaeidae) - Muhammad Javaid; Unsar Naeem-Ullah; Waheed S. Khan; Shafqat Saeed; Mirza Abdul Qayyum; Muhammad Arslan Khan (International Journal of Tropical Insect Science, 2023)

Antagonistic impact on cadmium stress in alfalfa supplemented with nano-zinc oxide and biochar via upregulating metal detoxification - Hafiz Abdul Kareem; Muhammad Adeel; Muhammad Azeem; Muhammad Arslan Ahmad; Noman Shakoor; Mahmood Ul Hassan; Sana Saleem; Annie Irshad; Junpeng Niu; Zhipeng Guo; Ćupina Branko; Roman Hołubowicz; et al. (Journal of Hazardous Materials, 2023)

Fate of dissolved organics and generated sulfate ions during biofiltration of oil sands process water pretreated with sulfate radical advanced oxidation process - Muhammad Arslan; Soliu O. Ganiyu; Dustin M.E. Lillico; James L. Stafford; Mohamed Gamal El-Din (Chemical Engineering Journal, 2023)

Production performance, protein digestibility, gut health and economic efficiency in sexed broilers with super dozing of lysine - Najam us Sahar; Muhammad Shoaib; Muhammad Aslam Mirza; Shaukat Ali Bhatti; Shahzad Ashraf; Noreen Aslam; Alishbah Roobi; Muhammad Arslan Asif (Tropical Animal Health and Production, 2023)

Understanding the dynamics of capital structure, corporate governance, and corporate social responsibility in high- and low-leveraged US and Chinese firms - Ahmad Nawaz Mahmood; Hafiz Muhammad Arslan; Zahid Irshad Younas; Bushra Komal; Kamran Ali; Muhammad Mubeen (Environmental Science and Pollution Research, 2023)

Interplay of higher plants with lithium pollution: Global trends, meta-analysis, and perspectives - Noman Shakoor; Muhammad Adeel; Imran Azeem; Muhammad Arslan Ahmad; Muhammad Zain; Aown Abbas; Muzammil Hussain; Yaqi Jiang; Pingfan Zhou; Yuanbo Li; Ming Xu; Yukui Rui (Chemosphere, 2023)

Environment relevant concentrations of lithium influence soybean development via metabolic reprogramming - Noman Shakoor; Muhammad Adeel; Muhammad Arslan Ahmad; Muzammil Hussain; Imran Azeem; Muhammad Zain; Pingfan Zhou; Yuanbo Li; Ming Xu; Yukui Rui (Journal of Hazardous Materials, 2023)

Study on cinnamon essential oil release performance based on pH-triggered dynamic mechanism of active packaging for meat preservation - Junjun Zhang; Jianing Zhang; Xiaowei Huang; Jiyong Shi; Arslan Muhammad; Xiaodong Zhai; Jianbo Xiao; Zhihua Li; Megan Povey; Xiaobo Zou (Food Chemistry, 2023)

Analysis of Temperature Data Using the Innovative Trend Pivot Analysis Method and Trend Polygon Star Concept: A Case Study of Soan River Basin, Potohar, Pakistan - Fiaz Hussain; Ray-Shyan Wu; Ghulam Nabi; Rana Shahzad Noor; Muhammad Naveed Anjum; Muhammad Azam; Arslan Afzal (Pure and Applied Geophysics, 2023)
The trend analysis approach is used to estimate changing climate and its impact on the environment, agriculture and water resources. Innovative polygonal trend analyses are qualitative methods applied to detect changes in the environment. In this study, the Innovative Trend Pivot Analysis Method (ITPAM) and Trend Polygon Star Concept Method were applied for temperature trend detection in Soan River Basin (SRB), Potohar region, Pakistan. The average monthly temperature data (1995–2020) for 11 stations were used to create polygon graphics. Trend length and slope were calculated separately for arithmetic mean and standard deviation. The innovative methods produced useful scientific information, with the identification of monthly shifts and trend behaviors of temperature data at different stations. Some stations showed an increasing trend and others showed decreasing behavior. This increasing and decreasing variability is the result of climate change. The winter season temperature is increasing, and the months of December to February are getting warmer. Summer is expanding and pushing autumn towards winter, swallowing the early period of the cold season. The monthly polygonal trends with risk graphs depicted a clear picture of climate change in the Potohar region of Pakistan. The phenomena of observed average temperature changes, indicated by both qualitative methods, are interesting and have the potential to aid water managers’ understanding of the cropping system of the Potohar region.

An overview of genome-wide association mapping studies in Poaceae species (model crops: wheat and rice) - Muhammad Abu Bakar Zia; Muhammad Farhan Yousaf; Arslan Asim; Muhammad Naeem (Molecular Biology Reports, 2022)

A quantitative assessment of pollution from potentially toxic elements in groundwater and the accompanying health risks - Atif Muhmood; Abdul Majeed; Abid Niaz; Asrar Hussain Shah; Ali Afzal; Khaliq ur Rehman Arshad; Muhammad Rashid; Arslan Nazarat (Arabian Journal of Geosciences, 2022)

Impact assessment of watercourse rehabilitation programs in Sindh, Pakistan using geospatial techniques - Arjumand Z. Zaidi; Sumaira Zafar; Muhammad Arslan; Saad Malik; Sana Ullah Shah; Asmat Ullah (Arabian Journal of Geosciences, 2022)

Exogenous menadione sodium bisulphite alleviates detrimental effects of alkaline stress on wheat (Triticum aestivum L.) - Ali Akbar; Muhammad Arslan Ashraf; Rizwan Rasheed; Iqbal Hussain; Shafaqat Ali; Abida Parveen (Physiology and Molecular Biology of Plants, 2022)

Nexus between environmental disclosures and top management team characteristics: a systematic review - Hafiz Muhammad Arslan; Ye Chengang; Bushra Komal; Songsheng Chen (Environmental Science and Pollution Research, 2022)

Situational assessment for fecal sludge management in major cities of Pakistan - Nida Maqbool; Muhammad Arslan Shahid; Sher Jamal Khan (Environmental Science and Pollution Research, 2022)

Understanding the dynamics of natural resources rents, environmental sustainability, and sustainable economic growth: new insights from China - Hafiz Muhammad Arslan; Irfan Khan; Muhammad Irfan Latif; Bushra Komal; Songsheng Chen (Environmental Science and Pollution Research, 2022)

Efficient photocatalytic degradation of nitrobenzene by copper-doped TiO2: kinetic study, degradation pathway, and mechanism - Tehmina Akhtar; Habib Nasir; Effat Sitara; Syeda Aqsa Batool Bukhari; Sharif Ullah; Rana Muhammad Arslan Iqbal (Environmental Science and Pollution Research, 2022)

Choline Chloride Mediates Chromium Tolerance in Spinach (Spinacia oleracea L.) by Restricting its Uptake in Relation to Morpho-physio-biochemical Attributes - Iqbal Hussain; Muhammad Hamzah Saleem; Sahar Mumtaz; Rizwan Rasheed; Muhammad Arslan Ashraf; Faisal Maqsood; Muzammal Rehman; Humaira Yasmin; Shakeel Ahmed; Muhammad Ishtiaq; Sana Anwar; Shafaqat Ali (Journal of Plant Growth Regulation, 2022)

Taurine modulates dynamics of oxidative defense, secondary metabolism, and nutrient relation to mitigate boron and chromium toxicity in Triticum aestivum L. plants - Muhammad Arslan Ashraf; Rizwan Rasheed; Iqbal Hussain; Muhammad Iqbal; Muhammad Umar Farooq; Muhammad Hamzah Saleem; Shafaqat Ali (Environmental Science and Pollution Research, 2022)

Fertigation of calcium nitrate [Ca(NO3)2] confers metal tolerance in two chickpea (Cicer arietinum L.) cultivars - Abida Parveen; Iqbal Hussain; Shagufta Perveen; Muhammad Arslan Ashraf; Rizwan Rasheed; Saddam Hussain; Sajjad Hussain; Sumaira Thind; Arshad Ali; Zahid Ullah; Qaisar Mahmood (Arabian Journal of Geosciences, 2022)

Appraisal of CO2 emission in Tunisia’s industrial sector: a dynamic vector autoregression method - Besma Talbi; Muhammad Ramzan; Hafiz Arslan Iqbal; Buhari Doğan (Environmental Science and Pollution Research, 2022)

Environmental pollution and agricultural productivity in Pakistan: new insights from ARDL and wavelet coherence approaches - Muhammad Ramzan; Hafiz Arslan Iqbal; Muhammad Usman; Ilhan Ozturk (Environmental Science and Pollution Research, 2022)

Competency of groundwater recharge of irrigated cotton field subjacent to sowing methods, plastic mulch, water productivity, and yield under climate change - Muhammad Saeed; Ahsan Maqbool; Muhammad Adnan Ashraf; Muhammad Arshad; Kashif Mehmood; Muhammad Usman; Muhammad Arslan Farid (Environmental Science and Pollution Research, 2022)
Irrigated agriculture is a foremost consumer of water resources to fulfill the demand for food and fiber with an increasing population under climate changes; cotton is no exception. Depleting groundwater recharge and water productivity is critical for the sustainable cotton crop yield peculiarly in the semiarid region. This study investigated the water productivity and cotton yield under six different treatments: three sowing methods, i.e., flat, ridge, and bed planting with and without plastic mulch. Cotton bed planting without mulch showed maximum water productivity (0.24 kg.m −3 ) and the highest cotton yield (1946 kg.ha −1 ). Plastic mulching may reduce water productivity and cotton yield. HYDRUS-1D unsaturated flow model was used to access the groundwater recharge for 150 days under six treatments after model performance evaluation. Maximum cumulative recharge was observed 71 cm for the flat sowing method without plastic mulch. CanESM2 was used to predict climate scenarios for RCP 2.6, 4.5, and 8.5 for the 2050s and 2080s by statistical downscale modeling (SDSM) using historical data from 1975 to 2005 to access future groundwater recharge flux. Average cumulative recharge flux declined 36.53% in 2050 and 22.91% in 2080 compared to 2017 without plastic mulch. Multivariate regression analysis revealed that a maximum 23.78% reduction in groundwater recharge could influence future climate change. Further study may require to understand the remaining influencing factor of depleting groundwater recharge. Findings highlight the significance of climate change and the cotton sowing method while accessing future groundwater resources in irrigated agriculture.

A study on the contamination assessment, health risk and mobility of two heavy metals in the soil-plants-ruminants system of a typical agricultural region in the semi arid environment - Xiaoping Ge; Zafar Iqbal Khan; Fu Chen; Mubeen Akhtar; Kafeel Ahmad; Abid Ejaz; Muhammad Arslan Ashraf; Muhammad Nadeem; Shahzad Akhtar; Jawaher Alkahtani; Yheni Dwiningsih; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Soil conditioners improve rhizodegradation of aged petroleum hydrocarbons and enhance the growth of Lolium multiflorum - Fida Hussain; Aqib Hassan Ali Khan; Imran Hussain; Asifa Farooqi; Yousaf Shad Muhammad; Mazhar Iqbal; Muhammad Arslan; Sohail Yousaf (Environmental Science and Pollution Research, 2022)

Salinity modulates lead (Pb) tolerance and phytoremediation potential of quinoa: a multivariate comparison of physiological and biochemical attributes - Azka Iftikhar; Ghulam Abbas; Muhammad Saqib; Arslan Shabbir; Muhammad Amjad; Muhammad Shahid; Iftikhar Ahmad; Shahid Iqbal; Saeed Ahmad Qaisrani (Environmental Geochemistry and Health, 2022)

Spatio-temporal variability of drought characteristics across Pakistan - Jae Eun Lee; Muhammad Azam; Saif Ur Rehman; Muhammad Waseem; M. Naveed Anjum; Arslan Afzal; M. J. M. Cheema; Muhammad Mehtab; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Abid Sarwar; et al. (Paddy and Water Environment, 2022)

Does digitalization matter in green preferences in nexus of output volatility and environmental quality? - Carlos Samuel Ramos-Meza; Rinat Zhanbayev; Hazrat Bilal; Mubbashra Sultan; Zehra Betül Pekergin; Hafiz Muhammad Arslan (Environmental Science and Pollution Research, 2021)

Bio-purification of sugar industry wastewater and production of high-value industrial products with a zero-waste concept - Muhammad Zohaib Nawaz; Muhammad Bilal; Arslan Tariq; Hafiz M. N. Iqbal; Huda Ahmed Alghamdi; Hairong Cheng (Critical Reviews in Food Science and Nutrition, 2021)

The environmental sustainability effects of financial development and urbanization in Latin American countries - Tomiwa Sunday Adebayo; Muhammad Ramzan; Hafiz Arslan Iqbal; Abraham Ayobamiji Awosusi; Gbenga Daniel Akinsola (Environmental Science and Pollution Research, 2021)

Characterization of Mercury-Resistant Rhizobacteria for Plant Growth Promotion: An In Vitro and In Silico Approach - Aatif Amin; Muhammad Naveed; Umair Munawar; Arslan Sarwar; Zakia Latif (Current Microbiology, 2021)

Genomic features of a high-risk mcr-1.1-positive Escherichia coli ST10 isolated from cattle farm environment - Arslan Ali; Herrison Fontana; Elder Sano; Ruichao Li; Muhammad Humayon; Sadeequr Rahman; Nilton Lincopan; Mashkoor Mohsin (Environmental Science and Pollution Research, 2021)

Do risk perceptions and constraints influence the adoption of climate change practices among small livestock herders in Punjab, Pakistan? - Muhammad Faisal; Xia Chunping; Azhar Abbas; Muhammad Haseeb Raza; Shoaib Akhtar; Muhammad Arslan Ajmal; Abdelrahman Ali (Environmental Science and Pollution Research, 2021)

Menadione sodium bisulfite alleviated chromium effects on wheat by regulating oxidative defense, chromium speciation, and ion homeostasis - Sajjad Hassan Askari; Muhammad Arslan Ashraf; Shafaqat Ali; Muhammad Rizwan; Rizwan Rasheed (Environmental Science and Pollution Research, 2021)

Alleviation of cadmium stress by silicon nanoparticles during different phenological stages of Ujala wheat variety - Sumaira Thind; Iqbal Hussain; Rizwan Rasheed; Muhammad Arslan Ashraf; Abida Perveen; Allah Ditta; Saddam Hussain; Nighat Khalil; Zahid Ullah; Qaisar Mahmood (Arabian Journal of Geosciences, 2021)

Menadione sodium bisulphite regulates physiological and biochemical responses to lessen salinity effects on wheat (Triticum aestivum L.) - Ali Akbar; Muhammad Arslan Ashraf; Rizwan Rasheed; Shafaqat Ali; Muhammad Rizwan (Physiology and Molecular Biology of Plants, 2021)

Fluoride and arsenic contamination in drinking water due to mining activities and its impact on local area population - Tasawar Ali Chandio; Muhammad Nasiruddin Khan; Maria Taj Muhammad; Ozcan Yalcinkaya; Agha Arslan Wasim; Ahmet Furkan Kayis (Environmental Science and Pollution Research, 2021)

Influence of IP-injected ZnO-nanoparticles in Catla catla fish: hematological and serological profile - Tariq Munir; Muhammad Latif; Arslan Mahmood; Arif Malik; Fahad Shafiq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Modeling smallholder livestock herders’ intentions to adopt climate smart practices: An extended theory of planned behavior - Muhammad Faisal; Xia Chunping; Shoaib Akhtar; Muhammad Haseeb Raza; Muhammad Tariq Iqbal Khan; Muhammad Arslan Ajmal (Environmental Science and Pollution Research, 2020)

Bioaccumulation of ytterbium oxide nanoparticles insinuate oxidative stress, inflammatory, and pathological lesions in ICR mice - Muhammad Adeel; Jin Tingting; Tariq Hussain; Xiao He; Muhammad Arslan Ahmad; Muhammad Kashif Irshad; Noman Shakoor; Peng Zhang; Xie Changjian; Yi Hao; Zhang Zhiyong; Rabia Javed; et al. (Environmental Science and Pollution Research, 2020)

Interactive effects of chitosan and cadmium on growth, secondary metabolism, oxidative defense, and element uptake in pea (Pisum sativum L.) - Rizwan Rasheed; Muhammad Arslan Ashraf; Asma Arshad; Muhammad Iqbal; Iqbal Hussain (Arabian Journal of Geosciences, 2020)

First report of brown leaf spot of rice caused by Curvularia spicifera in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Muhammad Atiq; Muhammad Zeeshan Mansha; Hafiz Muhammad Aatif; Hafiz Arslan Anwaar; Khalid Naveed (Journal of Plant Pathology, 2020)

Cadmium Partitioning, Physiological and Oxidative Stress Responses in Marigold (Calendula calypso) Grown on Contaminated Soil: Implications for Phytoremediation - Amjad Farooq; Muhammad Nadeem; Ghulam Abbas; Arslan Shabbir; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Farhan Saeed; Ahsan Akram; Adnan Younis; Gulzar Akhtar (Bulletin of Environmental Contamination and Toxicology, 2020)

Exogenously applied 5-aminolevulinic acid modulates growth, secondary metabolism and oxidative defense in sunflower under water deficit stress - Rizwan Rasheed; Humaira Yasmeen; Iqbal Hussain; Muhammad Iqbal; Muhammad Arslan Ashraf; Abida Parveen (Physiology and Molecular Biology of Plants, 2020)

Foliar applied fullerol differentially improves salt tolerance in wheat through ion compartmentalization, osmotic adjustments and regulation of enzymatic antioxidants - Fahad Shafiq; Muhammad Iqbal; Muhammad Arslan Ashraf; Muhammad Ali (Physiology and Molecular Biology of Plants, 2020)

Effective plant-endophyte interplay can improve the cadmium hyperaccumulation in Brachiaria mutica - Muhammad Tayyab Ahsan; Razia Tahseen; Abida Ashraf; Abid Mahmood; Muhammad Najam-ul-haq; Muhammad Arslan; Muhammad Afzal (World Journal of Microbiology and Biotechnology, 2019)

Seed Pre-treatment with Polyhydroxy Fullerene Nanoparticles Confer Salt Tolerance in Wheat Through Upregulation of H2O2 Neutralizing Enzymes and Phosphorus Uptake - Fahad Shafiq; Muhammad Iqbal; Muhammad Ali; Muhammad Arslan Ashraf (Journal of Soil Science and Plant Nutrition, 2019)

Exogenous menadione sodium bisulfite mitigates specific ion toxicity and oxidative damage in salinity-stressed okra (Abelmoschus esculentus Moench) - Muhammad Arslan Ashraf; Hafiza Farhat Asma; Muhammad Iqbal (Acta Physiologiae Plantarum, 2019)

Removal of pharmaceuticals and personal care products using constructed wetlands: effective plant-bacteria synergism may enhance degradation efficiency - Phuong Minh Nguyen; Muhammad Afzal; Inaam Ullah; Naeem Shahid; Mujtaba Baqar; Muhammad Arslan (Environmental Science and Pollution Research, 2019)

Opportunities and challenges in the remediation of metal-contaminated soils by using tobacco (Nicotiana tabacum L.): a critical review - Muhammad Zia ur Rehman; Muhammad Rizwan; Muhammad Irfan Sohail; Shafaqat Ali; Aisha A. Waris; Hinnan Khalid; Asif Naeem; Hamaad Raza Ahmad; Arslan Rauf (Environmental Science and Pollution Research, 2019)

Enhanced degradation of hydrocarbons by gamma ray induced mutant strain of Pseudomonas putida - Razia Tahseen; Muhammad Arslan; Samina Iqbal; Zafar M. Khalid; Muhammad Afzal (Biotechnology Letters, 2019)

First report of Alternaria alternata causing postharvest fruit rot of peach in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Aman Ullah Malik; Sidra Aslam; Mubeen Sarwar; Sajid Ali; Muhammad Arslan Khan; Akhtar Hameed; Sohaib Sarfraz (Journal of Plant Pathology, 2019)

Multi-precursory Analysis of Phalla Earthquake (July 2015; Mw 5.1) Near Islamabad, Pakistan - Adnan Barkat; Aamir Ali; Khaista Rehman; Muhammad Awais; Muhammad Arslan Tariq; Junaid Ahmed; Muhammad Ayaz Amin; Talat Iqbal (Pure and Applied Geophysics, 2018)

Exogenously applied zinc and copper mitigate salinity effect in maize (Zea mays L.) by improving key physiological and biochemical attributes - Muhammad Naveed Iqbal; Rizwan Rasheed; Muhammad Yasin Ashraf; Muhammad Arslan Ashraf; Iqbal Hussain (Environmental Science and Pollution Research, 2018)

Effect of breeding method and season on pregnancy rate and embryonic and fetal losses in lactating Nili-Ravi buffaloes - Arslan Qayyum; Usman Arshad; Muhammad Rizwan Yousuf; Nasim Ahmad (Tropical Animal Health and Production, 2018)

Biology and management of Avena fatua and Avena ludoviciana: two noxious weed species of agro-ecosystems - Ali Ahsan Bajwa; Muhammad Javaid Akhter; Nadeem Iqbal; Arslan Masood Peerzada; Zarka Hanif; Sudheesh Manalil; Saima Hashim; Hafiz Haider Ali; Lynda Kebaso; David Frimpong; Halima Namubiru; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2017)

Foliar application of selenium increases fertility and grain yield in bread wheat under contrasting water availability regimes - Iram Shahzadi; Muhammad Iqbal; Rizwan Rasheed; M. Arslan Ashraf; Shagufta Perveen; Makhdoom Hussain (Acta Physiologiae Plantarum, 2017)

Does exogenous application of ascorbic acid modulate growth, photosynthetic pigments and oxidative defense in okra (Abelmoschus esculentus (L.) Moench) under lead stress? - Iqbal Hussain; Asif Siddique; Muhammad Arslan Ashraf; Rizwan Rasheed; Muhammad Ibrahim; Muhammad Iqbal; Sobia Akbar; Muhammad Imran (Acta Physiologiae Plantarum, 2017)

Low C/N ratio raw textile wastewater reduced labile C and enhanced organic-inorganic N and enzymatic activities in a semiarid alkaline soil - Mahnaz Roohi; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Muhammad Arslan Ashraf; Muhammad Atif Riaz; Ishaq A. Mian (Environmental Science and Pollution Research, 2017)

Plant–bacteria partnerships for the remediation of persistent organic pollutants - Muhammad Arslan; Asma Imran; Qaiser Mahmood Khan; Muhammad Afzal (Environmental Science and Pollution Research, 2017)

Growth stage-based modulation in physiological and biochemical attributes of two genetically diverse wheat (Triticum aestivum L.) cultivars grown in salinized hydroponic culture - Muhammad Arslan Ashraf; Muhammad Ashraf (Environmental Science and Pollution Research, 2016)

Benthic foraminifera in sandy (siliciclastic) coastal sediments of the Arabian Gulf (Saudi Arabia): a technical report - Muhammad Arslan; Michael A. Kaminski; Bassam S. Tawabini; Muhammad Ilyas; Fabrizio Frontalini (Arabian Journal of Geosciences, 2016)

Exogenous application of silicon at the boot stage decreases accumulation of cadmium in wheat (Triticum aestivum L.) grains - Iqbal Hussain; Muhammad Arslan Ashraf; Rizwan Rasheed; Anum Asghar; Muhammad Asim Sajid; Muhammad Iqbal (Brazilian Journal of Botany, 2015)

Physiological and biochemical markers to optimize sugar mill wastewater for irrigation in maize (Zea mays L.) crop - Rizwan Rasheed; Muhammad Arslan Ashraf; Iqbal Hussain; Abida Parveen; Rizwan Alam; Muhammad Iqbal (Brazilian Journal of Botany, 2015)

Exogenous proline and glycinebetaine mitigate cadmium stress in two genetically different spring wheat (Triticum aestivum L.) cultivars - Rizwan Rasheed; Muhammad Arslan Ashraf; Iqbal Hussain; Muhammad Zulqurnain Haider; Uzma Kanwal; Muhammad Iqbal (Brazilian Journal of Botany, 2014)

Time-course changes in growth and biochemical indices of mung bean [Vigna radiata (L.) Wilczek] genotypes under salinity - Syed Hammad Raza; Muhammad Bilal Ahmad; Muhammad Arslan Ashraf; Fahad Shafiq (Brazilian Journal of Botany, 2014)

Expression patterns of miR-221 and its target Caspase-3 in different cancer cell lines - Sercan Ergun; Kaifee Arman; Ebru Temiz; İbrahim Bozgeyik; Önder Yumrutaş; Muhammad Safdar; Hasan Dağlı; Ahmet Arslan; Serdar Oztuzcu (Molecular Biology Reports, 2014)